Ekspresi IL – 1β pada Proses Kesembuhan Fraktur Os Femur Tikus Putih (Rattus norvegicus) Ovariektomi yang Diterapi dengan Ekstrak Cikal Tulang (Cissus quadrangularis) - Ira Sari Yudaniayanti; Bambang Sektiari Lukiswanto; M. Zainal Arifin (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
This study aims to determine the potential of the Cissus quadrangularis extract to decreased the expression of IL-1 β so that it can to inhibit bone resorption and osteoporosis fracture healing is not delayed union. Forty rats adapted for 1 week, and then divided into four groups with 10 replications. P0 (sham-operated + Osteotomy + CMC Na); P1 (ovariectomy + Osteotomy + CMC Na); P2 (ovariectomy + Osteotomy + Raloxifene 5.4 mg /kg); P3 (ovariectomy + Osteotomy + CQ 750 mg / kg). Osteoporosis induced is made by bilateral ovariectomy in rats, then to make sure that osteoporosis is already happened, 8 weeks post-ovariectomy performed radiology examinations on the femur, then the osteotomy action. IL1-β expression observations performed in at the 2nd week and 6th week after osteotomy through the immunohistochemistry examination. The results of immunohistochemistry examination in the 2nd week showed an increased expression of IL1-β in all groups of rat that did ovariectomy (P1, P2 and P3) were significantly different (p <0.05) with a rat group that didn’t ovariectomy, as well P2 dan P3 were significantly different with P1. The Results of immunohistochemistry examination in the 6th week showed the samepattern with the 2nd week and there is increased IL1-β expression in all groups of rat compared with the results of the examination in the 2nd week. Based on these results it can be concluded that Cissus quadrangularis extract andRaloxifen can decreased the expression of IL-1 β, and the results that don’t significantly different, so that these both materials can to inhibit bone resorption and osteoporosis fracture healing don’t get delayed union.